Embracing Transculturalism and Footnoting Islam in Accounts of Arab Migration to Cuba. Issue 1 (2nd January 2016) - Fiddian-Qasmiyeh, Elena
Abstract : This essay traces the development of Cuban analyses of Arab migration to the island from the 1500s to the present. It examines whether there is a specifically 'Cuban' school of 'migration studies', analysing the nature and implications of Ortiz's concept of transculturation underpinning the postcolonial development of 'Cuban national identity'. It further argues that, despite official Cuban claims regarding post-revolutionary racial equality, Arab migration has not only been historically and politically marginalized in accounts of the development of 'Cuban identity', including in Ortiz's own work, but diverse 'waves' of Arab migration to the island have been characterized by what I refer to, following Derrida, as the accumulative 'footnoting of Islam'. In conclusion, I argue that Muslim Arab immigration prior to the Cuban Revolution has been entirely overshadowed by a systematic focus on Christian Arabs, in effect leading to the category 'Arab' being practically synonymous with 'Christian' or 'Maronite', with wide-ranging implications for our understanding of Cuba's academic and political discourses regarding national identity in the twentieth and twenty-first centuries.